Zika and dengue but not chikungunya are associated with Guillain-Barré syndrome in Mexico: A case-control study. - Israel Grijalva; Concepción Grajales-Muñiz; César González-Bonilla; Victor Hugo Borja-Aburto; Martín Paredes-Cruz; José Guerrero-Cantera; Joaquín González-Ibarra; Alfonso Vallejos-Parás; Teresita Rojas-Mendoza; Clara Esperanza Santacruz-Tinoco; Porfirio Hernández-Bautista; Lumumba Arriaga-Nieto; et al. (Public Library of Science (PLoS), 2020)
Background Zika, dengue and chikungunya viruses (ZIKV, CHIKV and DENV) are temporally associated with neurological diseases, such as Guillain-Barré syndrome (GBS). Because these three arboviruses coexist in Mexico, the frequency and severity of GBS could theoretically increase. This study aims to determine the association between these arboviruses and GBS in a Mexican population and to establish the clinical characteristics of the patients, including the severity of the infection. A case-control study was conducted (2016/07/01-2018/06/30) in Instituto Mexicano del Seguro Social (Mexican Social Security Institute) hospitals, using serum and urine samples that were collected to determine exposure to ZIKV, DENV, CHIKV by RT-qPCR and serology (IgM). For the categorical variables analysis, Pearson's χ2 or Fisher exact tests were used, and the Mann-Whitney U test for continuous variables. To determine the association of GBS and viral infection diagnosis through laboratory and symptomatology before admission, we calculated the odds ratio (OR) and 95% confidence intervals (95%CI) using a 2x2 contingency table. A p-value ≤ 0.05 was considered as significant. Ninety-seven GBS cases and 184 controls were included. The association of GBS with ZIKV acute infection (OR, 8.04; 95% CI, 0.89-73.01, p = 0.047), as well as laboratory evidence of ZIKV infection (OR, 16.45; 95% CI, 2.03-133.56; p = 0.001) or Flavivirus (ZIKV and DENV) infection (OR, 6.35; 95% CI, 1.99-20.28; p = 0.001) was observed. Cases of GBS associated with ZIKV demonstrated a greater impairment of functional status and a higher percentage of mechanical ventilation. According to laboratory results, an association between ZIKV or ZIKV and DENV infection in patients with GBS was found. Cases of GBS associated with ZIKV exhibited a more severe clinical picture. Cases with co-infection were not found.